1990
DOI: 10.1212/wnl.40.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic modeling of concentration‐effect relationships after controlled‐release carbidopa/levodopa (Sinemet CR4) in Parkinson's disease

Abstract: Eight parkinsonian patients participated in a pharmacokinetic pharmacodynamic study of sequential doses of controlled-release carbidopa (CD)/levodopa (LD) at 4-hour intervals, with serial blood samples obtained before and after each dose. Effect measurements obtained with each blood sample included tapping and walking speed as well as a global assessment of motor function. Analysis of the data by extended least squares regression for linear, Emax, and sigmoid Emax pharmacodynamic models revealed that linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…different score systems for the motor response), PK-PD studies on levodopa IIS,i6, [39][40][41] have demonstrated almost consistent findings. All studies prove the E max model to be suitable for describing the C-E relationship of levodopa.…”
Section: Studies On the Pk-po Relationship Of Levodopamentioning
confidence: 78%
“…different score systems for the motor response), PK-PD studies on levodopa IIS,i6, [39][40][41] have demonstrated almost consistent findings. All studies prove the E max model to be suitable for describing the C-E relationship of levodopa.…”
Section: Studies On the Pk-po Relationship Of Levodopamentioning
confidence: 78%
“…Analyses were first performed in strata defined by respondent type (proxy, nonproxy) and pooled only if results were similar. 36 Because smoking behavior may have changed as the result of early, undiagnosed PD, analyses also were performed for the periods 10 years and 20 years before the index date. Analyses of "total" tobacco exposure, including cigarettes, cigars, pipes, and chewing tobacco, also were performed for each of these strata.…”
mentioning
confidence: 99%
“…However, acute tolerance to levodopa does not appear to be the underlying cause as proteresis (i.e. clockwise hysteresis) was not present in the plasma drug concentrationeffect plots, and this phenomenon has not been reported by other authors who applied PK/PD-modeling to levodopa [1][2][3].…”
Section: Concentration-effect-analysismentioning
confidence: 74%
“…The equilibration half life of the effect compartment has been reported to about 30 min and a similar value was observed in our study when the IR preparation was given. Nelson et al [2] investigated the pharmacokinetic/dynamic relationship of levodopa after single dose administration of a CR-preparation. The mean EC50 was about 900 ng ml-' for improvement of walking speed and 1600 ng ml-' for the results of a finger tapping test.…”
Section: Concentration-effect-analysismentioning
confidence: 99%
See 1 more Smart Citation